Construcción e instalación de un prototipo para envasado y sellado de agua de mesa automatizado con arduino - Díaz Guerra, José Fernando (2024)
Automation with Arduino refers to the ability to use the Arduino IDE platform to control and perform tasks automatically, involving the interaction of sensors, actuators, and other devices. This allows the creation of automated solutions for various applications, ranging from simple projects to more complex systems. The purpose of this research was to build and install an efficient automated prototype for bottling and sealing table water using Arduino. This was achieved using the Proteus 8 Professional simulation program, Arduino IDE, and mathematical calculations. The result is an electrical design simulated when powered with the C++ programming language, achieving a performance of 98.27%, a precision of 1.73%, a prototype quality of up to 60%, and the creation of an interface in Visual Studio Community 2022. The conclusion drawn is that the use of the Arduino system is usefull and suitable for integration into manufacturing industries.